2020
DOI: 10.1126/science.abc6027
|View full text |Cite
|
Sign up to set email alerts
|

Impaired type I interferon activity and inflammatory responses in severe COVID-19 patients

Abstract: Coronavirus disease 2019 (COVID-19) is characterized by distinct patterns of disease progression suggesting diverse host immune responses. We performed an integrated immune analysis on a cohort of 50 COVID-19 patients with various disease severity. A unique phenotype was observed in severe and critical patients, consisting of a highly impaired interferon (IFN) type I response (characterized by no IFN-β and low IFN-α production and activity), associated with a persistent blood viral load and an exacerbated infl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

229
2,676
19
42

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,680 publications
(3,102 citation statements)
references
References 34 publications
229
2,676
19
42
Order By: Relevance
“…IFITMs are efficiently induced during the innate immune response in SARS-CoV-2 infected individuals (Blanco-Melo et al, Hadjadj et al, 2020). Consequently, the ability to utilize IFITMs as infection cofactor may play a key role in the ability of SARS-CoV-2 to invade the lower respiratory tract under inflammatory conditions, which represents a hallmark of severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…IFITMs are efficiently induced during the innate immune response in SARS-CoV-2 infected individuals (Blanco-Melo et al, Hadjadj et al, 2020). Consequently, the ability to utilize IFITMs as infection cofactor may play a key role in the ability of SARS-CoV-2 to invade the lower respiratory tract under inflammatory conditions, which represents a hallmark of severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Egr-1 was induced by both cytokines in PBMC and BMDM. These genes are involved in transcriptional regulation and integrating signal transduction pathways that are likely to play an important role in the cytokine storm and shift to hyperinflammatory gene expression in response to coronavirus infections (30,65).…”
Section: Regulation Of Genes By Interferon-α/β and Tnf-α In Bmdm Andmentioning
confidence: 99%
“…[15,16] Additionally, a recent investigation revealed that several severe cases of COVID-19 presented with a rare, X-chromosome lossof-function mutation that impaired Type I interferon response, [17] while another demonstrated an association between COVID-19 severity and Type I interferon deficiency. [18] Various studies have found reasons to support the use of Type I interferons in combination with other antivirals to promote positive outcomes among patients with COVID-19, but many are restricted by the number of patients they treated with interferon. [19] Interestingly, these interferons perform their functions by activating JAK pathway.…”
Section: Introductionmentioning
confidence: 99%